Anorexia nervosa e suas comorbilidades médicas - Eurico Miguel Casal Lima Basto (2021)
ABSTRACT Introduction: Anorexia nervosa is an eating disorder associated with various medical complications that contribute to it, being the psychiatric illness with the highest mortality rate. The aim of this work is to review the main medical complications of this disease. Methods: A bibliographic search was performed in PubMed and Scopus databases, using the following query: "anorexia nervosa" AND "medical complications". Other studies, considered relevant to this work, were added to the bibliography. Results: Anorexia nervosa is a multisystemic and debilitating disease. Most of its complications are resolved with nutricional rehabilitation and weight normalization, although some can cause permanent damage. Discussion: The numerous medical complications are responsible for more than half of the deaths and are the direct result of malnutrition and weight loss. Treatment is multidimensional and individualized for each patient. Early diagnosis and treatment are essential to obtain better results. Conclusions: It is essential that health professionals are aqcuainted with anorexia nervosa and its complications. Further studies are needed in order to improve the outcome of this psychiatric illness. Keywords: anorexia nervosa; medical complications